Regulation of credit rating agencies - Stolper, Anno (Journal of Banking & Finance, 2009)
Financial regulators recognize certain credit rating agencies for regulatory purposes. However, it is often argued that credit rating agencies have an incentive to assign inflated ratings. This paper studies a repeated principal-agent problem in which a regulator approves credit rating agencies. Credit rating agencies may collude to assign inflated ratings. Yet we show that there exists an approval scheme which induces credit rating agencies to assign correct ratings.